2016
DOI: 10.1037/a0039922
|View full text |Cite
|
Sign up to set email alerts
|

Thriving while engaging in risk? Examining trajectories of adaptive functioning, delinquency, and substance use in a nationally representative sample of U.S. adolescents.

Abstract: Recent advances in positive youth development theory and research explicate complex associations between adaptive functioning and risk behavior, acknowledging that high levels of both co-occur in the lives of some adolescents. However, evidence on nuanced overlapping developmental trajectories of adaptive functioning and risk has been limited to 1 sample of youth and a single conceptualization of adaptive functioning. We build on prior work by utilizing a nationally representative sample of U.S. adolescents (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
3
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 88 publications
6
20
3
5
Order By: Relevance
“…These findings are consistent with Warren et al. (), who found increases in substance use between the seventh and eighth grades for a subgroup (i.e., 30%) of a nationally representative sample of adolescents. Increases in alcohol use were also found among Chicago youth from ages 12 to 15 (Sacco, Bright, Jun, & Stapleton, ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These findings are consistent with Warren et al. (), who found increases in substance use between the seventh and eighth grades for a subgroup (i.e., 30%) of a nationally representative sample of adolescents. Increases in alcohol use were also found among Chicago youth from ages 12 to 15 (Sacco, Bright, Jun, & Stapleton, ).…”
Section: Discussionsupporting
confidence: 92%
“…Significant gender differences were found for delinquent behavior such that boys initially reported higher overall frequencies than girls, but reported greater decreases during summers compared to the school years. This is consistent with prior studies that have found that adolescent boys engage in more delinquent behavior than adolescent girls (e.g., Lewin‐Bizan et al., ; Warren et al., ), but suggests that these differences may be less apparent during the summer months.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations